O registo escondido num bairro em processo de realojamento: o caso dos Hindus da Quinta da Vitória - Cachado, R. (Etnográfica, 2013)
This paper results from an ethnography among the Hindu dwellers of a neighborhood in the outskirts of Lisbon. As dozens of other informal settlements, Quinta da Vitória was one of the neighborhoods included in the Special Re-housing Program (PER), and its inhabitants would be resettled in social housing. Comparing with other similar settlements, the PER process at Quinta da Vitória was too long. In this paper I will describe and analyze the ways by which the Hindu residents responded to this huge social housing policy in Portugal, which was meant to end up with all “shanty towns”. The main purpose of this paper is yet to explore James Scott’s (1990) conceptualization on subtle resistance and about the hidden transcript, its forms, and development into public forms of resistance. The article is also expected to contribute to the larger debate about social policies in Portugal.